The Role of Participatory Leadership in Achieving Quality Education in Educational Institutions: An Analytical Study (The International Journal of Educational Sciences and Arts, 2025)
This research aims to study the role of participatory leadership in achieving quality education in educational institutions. It also seeks to reveal the degree of application of this leadership in educational institutions, with a focus on the most important challenges facing the application of participatory leadership in educational institutions. The research was limited to the desk study and relied on the descriptive analytical approach, where previous studies were analyzed that dealt with participatory leadership and its positive role from multiple aspects: (achieving job satisfaction, achieving institutional excellence, effective decision-making, building a culture of quality), and studies that addressed the obstacles to implementing participatory leadership. Since one of the principles of quality is employee participation, studies were addressed in the quality of education to reveal the role of leadership in achieving quality in educational institutions. The results showed that the degree of application of participatory leadership was high in some educational institutions, and that participatory leadership plays a role in enhancing job satisfaction and motivating teachers, which raises the quality of education, and contributes to building a culture of quality by empowering workers and involving them in decisions, and supports the effectiveness of decision-making, which improves the quality of education, and plays a role in achieving institutional excellence and increasing administrative efficiency. The obstacles were represented by the lack of a culture of participatory leadership, the weakness of the cooperative work environment, the abundance of teaching and administrative burdens that limit teachers' participation, the weakness of leaders' conviction of the importance of participation, and the lack of training of leaders on modern leadership trends. The most important recommendations were to conduct more studies to enhance knowledge in this field and intensify training programs on participatory leadership, focusing on involving competent workers in planning and decision-making.
Keywords: Participatory Leadership; Quality of Education; Educational Institutions